Differential inheritance of pepper (Capsicum annuum) fruit pigments results in black to violet fruit colour. Issue 6 (8th August 2014) - Stommel, John R.; Pushko, Marija; Haynes, Kathleen G.; Whitaker, Bruce D.; Flachowsky, H.
Abstract Colour is a critical determinant of fruit and vegetable quality. We characterized the inheritance of black and violet immature pepper fruit colour and chlorophyll, carotenoid and anthocyanin pigments responsible for fruit colour. Segregation for black vs. violet fruit colour deviated from expectations for simple inheritance. The primary determinant of fruit colour was the concentration of chlorophyll and carotenoid pigments relative to anthocyanin concentration. Whereas anthocyanin concentration was 34% greater in violet fruit, chlorophyll and carotenoid concentrations were 20‐fold and fourfold greater, respectively, in black fruit relative to concentrations found in violet fruit. Measurement of Commission Internationale d'Eclairage (CIE) colour space scores revealed larger a* values and smaller b* values for violet fruit relative to corresponding parameters for black fruit. An additive–dominance model was sufficient to explain the variation in individual fruit pigments as well as the CIE parameter a*. Addition of additive × additive effects to the additive–dominance model resulted in the best‐fit model m[d][h][i] for L* and b* colour space parameters. For all pigment classes, significant additive effects contributed to the genetic variance for fruit colour.